NILAI KETAKTERATURAN TOTAL SISI DARI GRAF GUNUNG BERAPI - Sholehah, Rukmana; Slamin, S; Dafik, D (Department of Mathematics Education , University of Jember, 2015)
Abstract. For a simple undirected connected graph G(V,E) with vertex set V and edge set E a labeling  : V  E → 1, 2, 3, ..., k is called a total k-labeling. A total k-labeling is defined to be an edge irregular total k-labeling of the graph G if for every two different edges uv and xy of G there is t(uv) ≠ t(xy). The minimum k for which the graph G has an edge irregular total k-labeling is called the total edge irregularity strength of the graph G, denoted by tes(G). In this paper, we determine the total edge irregularity strength of volcano graph tes(Gbm,n) and the total edge irregularity strength of s copies volcano graph tes(sGbm,n). Key Words : edge irregular total labeling, total edge irregularity strength, volcano graph